2018
DOI: 10.1155/2018/8672357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermediate Stiffeners on the Behaviors of Partially Concrete Encased Steel Beams

Abstract: Partially concrete encased steel (PE) beams are composite steel beams and concrete elements that present several advantages, such as higher fire resistant, higher flexural capacity, and higher lateral torsional buckling resistant compared to bare steel beams. This paper reports an experimental study of eight PE beams under cyclic loading. The effectiveness of intermediate stiffeners, such as midspan stiffener and plastic hinge zone stiffener, in enhancing composite action and ductility of the PE beams was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Many researchers have studied the seismic behaviour of structural components [18][19][20]. Herrera et al [21] carried out a large-scale experimental study to investigate the cyclic behaviour of T-shaped moment-resisting frame (MRF) cantilever beams with openings placed in the midspan.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the seismic behaviour of structural components [18][19][20]. Herrera et al [21] carried out a large-scale experimental study to investigate the cyclic behaviour of T-shaped moment-resisting frame (MRF) cantilever beams with openings placed in the midspan.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] So far, numerous studies have been conducted on PEC beams and columns. [5][6][7][8][9][10][11][12][13] Mucedero et al [5] reported that the pushdown curve of the structure with PEC beams showed the feature of monotonically increasing due to apparent catenary action. Piquer and Hernández-Figueirido [13] found that the PEC column had good fire resistance and economy compared with the steel column with or without protection.…”
mentioning
confidence: 99%